Maximal oxygen uptake in well-trained and untrained 9-11 year-old children - Baltaci, G.; Ergun, N. (Pediatric Rehabilitation, 1997)
There is a world-wide trend for children to begin serious athletic training at progressively younger ages. Since there are no data concerning the cardiorespiratory function of Turkish children, the purpose of this study was to compare maximal oxygen uptake in well-trained and untrained children of similar ages. The trained subjects (20) were junior swimmers from a private college swimming team, and the untrained ones (20) were from the same school. Maximal oxygen uptake was directly measured during progressive treadmill exercise using open circuit spirometry. No significant differences in height, mass, and age were noted between the trained and untrained groups. Maximal aerobic power in absolute values and expressed per kilogram of body mass, was 19.57% and 20.06%, respectively: higher in the trained than in the untrained group (p < 0.05). These data suggest that physical training significantly increases maximal aerobic power in young subjects.